Versatile composite hydrogels for drug delivery and beyond - Chiang, Yi-Hua; Wu, Meng-Ju; Hsu, Wei-Chin; Hu, Teh-Min (Journal of materials chemistry. B, Materials for biology and medicine, 2020)
Hydrogels have extended applications across multiple fields. A novel hydrogel material is often evaluated for its properties and applications in either a wet or dry state, but not both. In this study, we investigated a protein-based, composite hydrogel system in both its wet and dry states. Bovine serum albumin (BSA) was used as the hydrogel base. With the assistance of organosilanes, BSA solutions became hydrogels under facile reaction conditions. In the first part, the wet gel was prepared in situ in a syringe; upon injecting through a needle, the gel retained its structure. The use of the nascent gel system as an injectable drug-delivery vehicle is of particular interest. We therefore developed a microplate platform that allows a "one-plate" study- i.e. gel preparation, payload loading and release-all being performed in a single plate. This one-plate method further enables a systematic study of various controlling parameters for drug release. For example, we can tune the release rate by simply adjusting the phosphate content in the hydrogel formulation. Besides, for low-releasing compounds, the release profile was also tunable while using the one-plate method. In the second part, we further demonstrate the versatility of our composite hydrogels. By simply varying the feed ratio of two organosilanes, (3-mercaptopropyl)methyldimethoxysilane and (3-mercaptopropyl)trimethoxysilane, and phosphate concentrations, dry gels exhibiting various absorption capacities towards water, organic solvents, and oil can be prepared. Further characterizations using SEM and 29 Si NMR spectroscopy revealed porous structures and hybrid siloxane bridges within the composite material. Albumin-organosilane composite hydrogels were prepared and characterized in both their wet and dry states. The wet gels were evaluated using an all-in-one-plate method for drug-delivery applications. Besides, the dry gels can withstand and absorb polar and nonpolar solvents.